EXSOLUTION TEXTURES IN ORTHOPYROXENE IN ALUMINOUS GRANULITES AS INDICATORS OF UHT METAMORPHISM: NEW EVIDENCE FROM THE EASTERN GHATS BELT, INDIA - Bose S.; Das K.; Dasgupta S.; Miura H.; Fukuoka M. (My University, 2006)
Highly aluminous orthopyroxene, coexisting with sapphirine, cordierite, sillimanite, quartz and garnet in various combinations, constitute granoblastic mosaic peak metamorphic assemblages in aluminous granulites from three localities in the Eastern Ghats Belt, India. Orthopyroxene contains four types of intergrowths: (a) involving sapphirine with or without cordierite, (b) involving spinel, but without sapphirine, (c) involving cordierite, but without sapphirine and spinel, and (d) involving garnet, without sapphirine, spinel or cordierite. On the basis of textural and compositional data, origin of the intergrowths is ascribed to breakdown of Mg-Tschermak component, locally also involving Fe- and Ti-Tschermak. An attempt is made to compute the "pre-breakdown" compositions of orthopyroxene by image analysis, which shows maximum Al2O3 content of 13.4 wt.% in the pristine orthopyroxene. Geothermometry, phase equilibria consideration and application of existing experimental data on alumina solubility in orthopyroxene coexisting with sapphirine and quartz, collectively indicate extreme thermal conditions of metamorphism (> 1000 °C) for the studied assemblages. This re-affirms the notion that Al2O3 solubility in orthopyroxene is the most powerful indicator of UHT metamorphism (Harley, S.L., 2004. Extending our understanding of ultrahigh temperature crustal metamorphism. J. Mineral. Petrol. Sci. 99, 140-158). The intergrowths are considered to have formed due to cooling from the thermal peak spanning a temperature range of approximately 150 °C. Appearance of diverse types of intergrowths is probably related to subtle differences in bulk composition, particularly Fe:Mg ratios. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALUMINOUS ORTHOPYROXENE; EASTERN GHATS; INTERGROWTH TEXTURES; UHT METAMORPHISM